La ricerca dell'identita - Bruno, Gianfranco; Palazzo Reale, Milano (Milano : Electa editrice, 1974)
Artaud, Antonin ; Bacon, Francis ; Barnes, Mary ; Beckmann, Max ; Bellmer, Hans ; Boccioni, Umberto ; Burri, Alberto ; Canogar, Rafael ; Corinthe, Lovis ; De Kooning, Willem ; Della Torre, Enrico ; Dix, Otto ; Dubuffet, Jean ; Ensor, James ; Ernst, Max ; Freud, Lucian ; Genoves, Juan ; Gerstl, Richard ; Heckel, Erich ; Hopper, Edward ; Kolig, Anton ; Michaux, Henri ; Meidner, Ludwig ; Radziwill, Franz ; Rainer, Arnulf ; etc.
La ricerca dell'identita, Palazzo Reale, Milano, 16 novembre 1974 - 15 gennaio 1975
boek